Studi Komparasi Layanan Smart City Antara Kota Semarang dan Kota Malang - Ajniver Hamnur Zebua; Aulia Surya Pertiwi; Ilmi Sulistiati Anisa; Muhammad Thoriq Ramadhani; Tria Rama Nabila; Irvan Arif Kurniawan (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Aulia Surya Pertiwi1, Ilmi Sulistiati Anisa2, Muhammad Thoriq Ramadhan3, Siti Wahyuni Rahmawati4, Tria Rama Nabila5, Irvan Arif Kurniawan6 Universitas Islam Syekh-Yusuf Tangerang, Fakultas Ilmu Sosial dan politik. Program studi Ilmu Administrasi Negara auliasryprtwi@gmail.com1, ilmysulistiatianisa@gmail.com2, rthoriq23@gmail.com3, yunnir016@gmail.com4, trianabila112@gmail.com5, iakurniawan@unis.ac.id6 ABSTRACT. A smart city is one that includes contemporary infrastructure and transportation systems, Additionally to human and social capital, create high-quality, long-term economic growth. The idea of the "Smart City" is becoming prevalent in major cities around the globe. This also applies to Indonesia. 2020 saw the release of the "Movement Towards 100 Smart Cities" by the Indonesian government. This was a significant milestone in the country's effort to digitize public services. Semarang City is one of the cities used as a model for the growth of smart cities in Indonesia. While it cannot be separated from that, one of the top aims for Malang Metropolis's development in 2022 is to realize a Smart City-based city. The chosen method is to use a literature review as a research strategy. In this literature study research, which is a series of events or activities related to library data collection methods, specifically by recording and processing research material taken from previous studies, the implementation of Smart City services in the cities of Semarang and Malang is being compared. In order to maximize the efficiency of creating a city, enhance the quality of life, and boost the local economy, the implementation of smart cities in the cities of Semarang and Malang has utilized and applied a universal method. Based on research supporting Cohen Boyd's "Smart City" theory, this is said. Keywords: Smart City, City Development, Semarang City, Malang City